From measurement to modelling in sport collisions - Preatoni, E.; Trewartha, G.; Cazzola, D.; Pain, M. T. G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This applied session presents an integrated approach for the analysis of sport collisions and comprises three main parts. In Section 1, practical examples from rugby activities (scrummaging, tackling) will be used to describe the issues related to in vivo measurement (e.g. preparation of the set-up, ecological validity, synchronisation, calibration) when impact events are observed and multiple players interact in a complex environment. The data needed to inform computer simulation modelling will also be discussed. In Section 2, attendees will be introduced to modelling with OpenSim (Delp et al, 2007) and a hands-on approach will be used to explore the potential of musculoskeletal modelling in the analysis of rugby-related events. In Section 3, the issue of giving an appropriate characterisation to the biomechanical model will be addressed. In particular, the activity will focus on the hypothesis of the human body as a system of rigid bodies vs. the inclusion in the model of soft tissues and wobbling masses, and the effect of such assumptions on the system dynamics in the presence of impacts will be explored.